Accuracy of machine learning models using ultrasound images in prostate cancer diagnosis - Christine, Christine; Fransiska, Fransiska (International Medical Journal Corp. Ltd, 2024)
Background: The literature on the accuracy of machine learning models using ultrasound images in prostate cancer diagnosis reveals a dynamic landscape marked by both significant advancements and persistent challenges. The introduction establishes the importance of integrating machine learning with ultrasound imaging to improve diagnostic precision, particularly in a domain fraught with high stakes due to the complexities associated with prostate cancer. The initial studies highlight the potential of machine learning to standardize interpretations, as evidenced by the comparative analysis of labeling strategies that demonstrated superior performance with digital pathologist annotations over radiologist labels (Bhattacharya et al., 2021). Literature Review: As the review progresses, it becomes clear that traditional ultrasound imaging faces limitations, such as low resolution and high inter-observer variability, which can compromise diagnostic accuracy (Akatsuka et al., 2022). The literature advocates for the application of artificial intelligence (AI) technologies to enhance the reliability of cancer grading, emphasizing the critical role of accurate pathological grading in treatment decision-making. Further analysis reveals a growing body of work focused on the integration of advanced machine learning techniques, including deep learning and hybrid models that combine traditional and innovative approaches (Luijten et al., 2022). Conclusion: In conclusion, the literature collectively underscores the transformative potential of machine learning and deep learning techniques in enhancing the accuracy of prostate cancer diagnosis using ultrasound images. Despite the promising advancements, the field faces critical challenges, particularly regarding the need for robust datasets, the integration of AI into clinical practice, and the necessity for standardized evaluation criteria. Addressing these challenges will be pivotal in realizing the full potential of AI technologies in improving diagnostic outcomes and patient management in prostate cancer.